Breakfast Eating Practices Among Doctors in Relation to their Nutritional Status - S. Sabahat Mansur, Aruna Ahmed (Journal of Rawalpindi Medical College, 2012)
Background: To compare the Body Mass Index(BMI) between regular breakfast eaters and irregular breakfast eaters among doctors when the whole day diet remains constant. Methods: In this cross sectional study information about diet, along with height (using stadeometer, or measuring tape), weight (by bathroom weight scale), of the participients, were recorded. With the help of height and weight, BMI was calculated. Based on BMI, nutritional status of the subjects were assessed keeping in view that the whole day dietary intake of the subjects remains constant. Results: Out of 351 respondent doctors, 68.7% were females. The age ranged from 25 to 59 years., Regular breakfast eaters (RBE) were 57.5%, 42.5% did not take breakfast regularly (IRBE). Gender difference did not have any impact on breakfast eating practices. Majority (32.9%) skipped due to lack of time .The mean BMI of regular breakfast eaters was 23.11±3.56 kg and of irregular breakfast eaters was 25.72±2.9 kg.. Conclusion: Regular breakfast eating is associated with lower BMI.